Hepatic control of perfusate homeostasis during normothermic extrocorporeal preservation. - St Peter, S; Imber, C; Kay, J; James, T; Friend, P; Peter, S (2003)
BACKGROUND: We investigated the ability of the isolated porcine liver to maintain acid-base homeostasis in the perfusate and the impact of ischemia-reperfusion injury without or with extracorporeal perfusion. METHODS: Harvested livers were either stored for 24 hours in cold University of Wisconsin solution or preserved by continuous, normothermic, oxygenated sanguineous perfusion with supplemental nutrition, prostacyclin, and bile salts. After a further 24-hour period of reperfusion of both groups on an extracorporeal circuit, the perfusate was assessed for both biochemical indices of synthetic and metabolic liver function as well as hepatocellular injury and blood gas analysis. RESULTS: Livers injured by cold ischemia during preservation displayed inferior synthetic and metabolic functions. Perfused livers, which displayed minimal ischemic injury, produced more bicarbonate than the cold-stored organs, suggesting autoregulation of pH homeostasis in perfused livers in contrast to progressively worsening acidosis in cold-stored organs. CONCLUSIONS: Given proper physiologic substrate the porcine liver has the ability to maintain acid-base homeostasis, provided there is not a significant ischemia-reperfusion injury.